Role of cation-exchange high-performance liquid chromatography in detection of hemoglobinopathies- a study of 500 cases in a tertiary care hospital - Babaria, Sneha Samir; Jarwani, Puja Bhavesh; Kothari, Sadhana Lalit; Patel, Shantibhai (Journal of Pathology of Nepal, 2021)
Background: Abnormalities of hemoglobin synthesis are among the most common inherited disorders. Cation exchange high-performance liquid chromatography offers a reliable tool for early, accurate detection thereby aiding in the prevention and management of thalassemia major and various hemoglobinopathies. Materials and methods: This was a retrospective study carried out in the Department of Pathology, GCSMC Hospital and Research center, Ahmedabad over six years from August 2013 to August 2019. 500 cases were studied for the identification of various hemoglobin disorders in patients referred for screening and detection of hemoglobinopathies. Results: Abnormal hemoglobin fractions were seen in 104/500 (20.8%) cases. The β thalassemia trait was the predominant abnormality with a total of 69 cases (66.3%). β thalassemia major, β thalassemia intermedia, Hb D Punjab- β thalassemia, Acquired Hb F and Hereditary persistence of fetal hemoglobin/δβ thalassemia trait was found in 1 case (0.96%) each. Sickle cell heterozygous was found in 9 cases (8.6%), Sickle cell homozygous in 5 cases (4.8%), and Sickle-ß thalassemia in 6 cases (5.8%). Other variants detected included Hb Q India heterozygous and Hb D Punjab heterozygous in 3 cases (2.9%) each and 2 cases (1.9%) of Hb E heterozygous and Hb J each. Conclusions: Cation exchange high-performance liquid chromatography is an ideal and widely used methodology for routine clinical laboratory because of the simplicity of the automated system. The majority of the abnormal cases are diagnosed with it except a few inconclusive cases for which molecular and genetic studies are required.